1995
DOI: 10.1111/j.1365-2427.1995.tb00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patterns of invertebrate stream drift in an Australian temperate stream

Abstract: 1. Invertebrate stream drift was sampled bimonthly in the Acheron River, Victoria, Australia, over a period of 18 months. Replicated hourly samples were collected over a 25-h period on each sampling date. A total of 194 taxa were identified in the drift. However, total drift density was dominated by few taxa. 2. Some evidence was obtained for a seasonal pattern in drift: this was most pronounced in relative abundances of individual taxa and the composition of the drift, rather than in total drift densities. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…However, we found higher drift densities in the dry winter season than in the wet summer season (Fig. 3(A)), corroborating the findings of Cowell and Carew (1976) and Schreiber (1995). Furthermore, we observed significant differences in taxonomic composition between seasons (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…However, we found higher drift densities in the dry winter season than in the wet summer season (Fig. 3(A)), corroborating the findings of Cowell and Carew (1976) and Schreiber (1995). Furthermore, we observed significant differences in taxonomic composition between seasons (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Drift densities of aquatic invertebrates were also consistently higher by night compared to day, although terrestrial invertebrate drift was higher by day than at night. Similar patterns of variation in drift density have been observed in other temperate streams (Sandlund, 1982;Obi & Connor, 1986;Schreiber, 1995;Shearer et al, 2002), although in some streams drift may be highest in spring to early autumn (Armitage, 1977;Stoneburner & Smock, 1979;Day et al, 1992) and in a few instances invertebrates drift density has been observed to be higher by day (Saltveit et al, 2001). Differences in species composition may explain discrepancies in the seasonal and diel patterns of drift observed between studies (Schrieber, 1995).…”
Section: Temporal Differences Of Invertebrate Driftsupporting
confidence: 61%
“…The information we do have on the dispersal behaviour of hydrobiosid larvae relevant to this study stream remains equivocal. Doeg and Milledge (1991) found hydrobiosids to be a relatively common component of the drift whereas Schreiber (1995) reported drift as uncommon (although mesh sizes in the latter study may not have been small enough to catch first-instar larvae). There is also some evidence to suggest that larvae are not rapid crawling colonisers of new substrate (Doeg et al 1989b).…”
Section: Discussionmentioning
confidence: 80%
“…Hydrobiosid larvae are relatively poor swimmers; however they are able to crawl considerable distances (personal observations) and have been reported in drift samples (Schreiber 1995). Given the potential for mobile larvae to relocate if eggs are deposited in unfavourable conditions, we might expect the fitness benefits conferred by specific oviposition behaviour to be related more closely to egg development and/or hatching success than larval survival.…”
Section: Discussionmentioning
confidence: 99%